Sulfur-tolerant shift catalyst as well as preparation method and application thereof

By using a sulfur-resistant transformation catalyst with Al2O3-MgAl2O4-CoAl2O4 support structure, combined with MoO3, CoO, MgO, Al2O3 and metal additive oxides, a strong synergistic catalytic reaction layer was formed, which solved the problem of methanation side reaction caused by the high temperature of the catalyst bed under high CO content and low water-gas ratio, and achieved high conversion reaction activity and low methanation reaction activity, reducing safety risks and activity instability.

CN119608138AActive Publication Date: 2025-03-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411821736.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

Under high CO content and low water-gas ratio process conditions, when the temperature of the catalyst bed is high, methanation side reactions are prone to occur, resulting in a decrease in the change reaction activity, an increase in the methanation reaction activity and a "flying temperature" of the bed temperature, which poses safety risks and activity stability problems.

Method used

The sulfur-resistant transformation catalyst with Al2O3-MgAl2O4-CoAl2O4 is used as the support structure. By adding MoO3, CoO, MgO, Al2O3 and metal additive oxides to the catalyst, a strong synergistic catalytic reaction layer is formed, the methanation reaction is inhibited, and the transformation reaction activity is improved.

Benefits of technology

It achieves high conversion reaction activity and low methanation reaction activity under high CO content and low water-gas ratio, avoids a sharp increase in the temperature of the catalyst bed, and reduces safety risks and activity instability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608138A_ABST
    Figure CN119608138A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, particularly relates to a sulfur-tolerant shift catalyst, and further discloses a preparation method and application of the sulfur-tolerant shift catalyst. The sulfur-tolerant shift catalyst provided by the invention has a special Al2O3-MgAl2O4-CoAl2O4 carrier structure, has high shift reaction activity and low methanation reaction activity, and can effectively solve the problem of low methanation reaction yield under the process conditions of high CO content and low water-gas ratio. The catalyst bed temperature is high, and methanation side reaction causes the adverse effects of reduction of shift reaction activity, increase of methanation reaction activity, 'temperature runaway 'of the bed temperature and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and specifically relates to a sulfur-resistant shift catalyst, and further discloses a preparation method and application thereof. Background Art

[0002] At present, carbon monoxide shift technology is mainly used in industrial production such as hydrogen production, synthetic methanol, synthetic ammonia, synthetic gasoline and city gas, among which shift catalyst plays a very important role. Due to the shortage and price increase of crude oil, high-sulfur substances such as coal, residual oil, and petroleum coke have gradually attracted people's attention as alternative raw materials for light hydrocarbons. With the development and progress of residual oil and coal gasification technology, especially the large-scale industrial application of water-coal slurry pressurized gasification technology, the research and development of sulfur-resistant shift catalysts has been further promoted. Since the 1960s, cobalt-molybdenum-based sulfur-resistant shift catalysts have been widely used due to their wide temperature range, sulfur resistance and high activity in CO shift reactions.

[0003] With the improvement of residual oil and coal gasification technology, especially the large-scale industrial application of new pressurized gasification technology, the CO content of effective gas component in process gas is getting higher and higher. Under the process conditions of high CO content and low water-gas ratio, when the catalyst bed temperature is higher than 350°C, methanation side reaction usually occurs. The reaction releases a large amount of heat, causing the bed temperature to increase sharply, which further aggravates the methanation side reaction, not only reducing the hydrogen content of the product and bringing the safety risk of overheating of the device, but also affecting the activity and activity stability of the catalyst. In recent years, the sulfur-resistant shift process mainly relies on adjusting process parameters to suppress the occurrence of methanation side reactions, such as adopting a high water-gas ratio shift process, distributing water to reduce the temperature and increasing the water-gas ratio at the same time, but the overall effect is minimal.

[0004] Studies have shown that spinel composite oxide AB2O4 has the advantages of stable crystal structure, high surface activity, and easy reaction with gas. In recent years, CoAl2O4 has been widely used in research due to its special structure and special properties. For example, Chinese patent CN1981927A discloses a cobalt-based Fischer-Tropsch synthesis catalyst and its preparation method. The catalyst has better C5 +Selectivity, but its application in cobalt-molybdenum sulfur-resistant conversion catalysts has not been studied. In addition, cobalt-molybdenum sulfur-resistant conversion catalysts are often modified with MgAl2O4 catalyst Al2O3 carriers. For example, Chinese patent CN104971731A discloses a wide temperature sulfur-resistant conversion catalyst and its preparation method, and the calcined product of magnesium aluminum hydrotalcite is used as a carrier for preparing the conversion catalyst. The conversion rate of CO obtained by the conversion catalyst can reach 87.62%. For example, Chinese patent CN110314675A discloses a modified alumina-based magnesium aluminum spinel and its preparation method and sulfur-resistant conversion catalyst. Although the catalyst overcomes the disadvantage of being easy to water and has good activity and stability in the temperature range of 200-500°C, it cannot reduce the selectivity of the methanation reaction under high temperature and low water-gas ratio conditions.

[0005] In summary, the art expects to develop a sulfur-tolerant shift catalyst with high shift reaction activity and low methanation reaction activity, which has very important application significance for the development of carbon monoxide shift technology. Summary of the invention

[0006] To this end, the technical problem to be solved by the present invention is to provide a sulfur-resistant shift catalyst, which has high shift reaction activity and low methanation reaction activity;

[0007] The second technical problem to be solved by the present invention is to provide a method for preparing the sulfur-resistant shift catalyst;

[0008] The third technical problem to be solved by the present invention is to provide application of the sulfur-resistant shift catalyst in a carbon monoxide shift process.

[0009] In order to solve the above technical problems, the present invention provides a sulfur-resistant shift catalyst, wherein the catalyst has a carrier structure as shown in Al2O3-MgAl2O4-CoAl2O4;

[0010] The sulfur-resistant shift catalyst comprises, based on the total amount, 6-12 wt% of MoO3, 3-4 wt% of CoO, 10-25 wt% of MgO, 57-80 wt% of Al2O3, and 2-10 wt% of metal promoter oxide.

[0011] Specifically, in the sulfur-resistant shift catalyst, the metal promoter oxide includes at least one of K2O, Zr2O or Ti2O.

[0012] The present invention also discloses a method for preparing a sulfur-resistant shift catalyst, comprising the following steps:

[0013] (1) mixing aluminum salt, cobalt salt and acid solution, and adding alcohol solution to dissolve them to obtain a mixed solution for standby use;

[0014] (2) mixing pseudo-boehmite and magnesium oxide to obtain a mixture for later use;

[0015] (3) kneading the mixed liquid and the mixed material to obtain a carrier precursor, and performing a first drying and a first calcination treatment to obtain a catalyst carrier;

[0016] (4) The catalyst carrier is immersed in an active solution containing a molybdenum salt and a metal promoter precursor, and subjected to a second drying and a second calcination treatment to obtain the desired catalyst.

[0017] Specifically, the method for preparing the sulfur-resistant shift catalyst comprises the following steps: in step (1), the cobalt salt (in the form of Co 2+ ) and the aluminum salt (in terms of Al 3+ The molar ratio of 1:2-3.

[0018] Specifically, the method for preparing the sulfur-resistant shift catalyst comprises the following steps: in step (1), the acid solution and the cobalt salt (in the form of Co 2+ The aluminum salt (in terms of Al 3+ The molar ratio of the total amount of the above-mentioned amount is 1:0.5-1.5, preferably 1:1;

[0019] Preferably, the acid comprises citric acid.

[0020] Specifically, in the method for preparing the sulfur-resistant shift catalyst, in the step (1), the alcohol solution includes an ethanol aqueous solution;

[0021] Preferably, the step (1) further comprises the step of evaporating and concentrating the mixed solution.

[0022] Specifically, in the method for preparing the sulfur-resistant shift catalyst, in the step (2), the magnesium oxide (Mg 2+ ) and the pseudo-boehmite (in terms of Al 3+ The molar ratio of 1:2-3.

[0023] Specifically, in the method for preparing the sulfur-resistant shift catalyst, in the step (3), the temperature of the first calcination step is 600-800° C., and the calcination time is 4-6 hours;

[0024] Preferably, the first drying temperature is 60-100° C., and the drying time is 10-15 hours.

[0025] Specifically, in the method for preparing the sulfur-resistant shift catalyst, in the step (4), the molybdenum salt (in the form of Mo 3+ ) and the cobalt salt (in Co 2+ The molar ratio of 2-3:1;

[0026] Preferably, the molybdenum salt comprises ammonium molybdate;

[0027] Preferably, the metal additive precursor comprises a nitrate of the metal additive, more preferably one of potassium nitrate, zirconium nitrate or metatitanic acid.

[0028] Specifically, in the method for preparing the sulfur-resistant shift catalyst, in the step (4), the temperature of the second calcination step is 400-600° C., and the calcination time is 2-4 hours;

[0029] Preferably, the second drying temperature is 60-100° C., and the drying time is 10-15 hours.

[0030] The present invention also discloses the use of the sulfur-resistant conversion catalyst or the sulfur-resistant conversion catalyst prepared by the method in a carbon monoxide conversion process.

[0031] The sulfur-resistant shift catalyst of the present invention has a special catalyst Al2O3-MgAl2O4-CoAl2O4 carrier structure; wherein CoAl2O4 can form a catalytic reaction layer with the active component Mo, producing a strong synergistic effect, so that the electronic interaction between molybdenum and CoAl2O4 is enhanced, and the H2 reduction peak of MoO3 appears between 515°C and 520°C, while the catalyst shows H2 reduction peaks of CoAl2O4 and MoO3 between 820°C and 830°C; at the same time, the addition of metal additives can synergistically constrain and stabilize Mo in the reaction in the presence of CoAl2O4, inhibit the reduction of Mo, reduce the adsorption of hydrogen by the catalyst, and improve the shift reaction activity while reducing the methanation reaction activity.

[0032] The sulfur-resistant shift catalyst of the present invention has high shift reaction activity and low methanation reaction activity, and can effectively solve the adverse effects of reduced shift reaction activity, increased methanation reaction activity, and "overheating" of the bed temperature caused by the methanation side reaction under high CO content and low water-gas ratio process conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0034] Figure 1 It is the H2-TPR spectra of the catalysts of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention.

[0036] Example 1

[0037] The method for preparing the sulfur-resistant shift catalyst described in this embodiment comprises the following steps:

[0038] (1) Pour 25.7 g of aluminum nitrate, 12 g of cobalt nitrate and 20.8 g of citric acid into a beaker, add an ethanol aqueous solution to completely dissolve them, and obtain a mixed solution, which is then stirred and evaporated in an aqueous solution at 80° C. to a certain volume;

[0039] (2) taking 78.6 g of pseudo-boehmite and 15 g of magnesium oxide and mixing them evenly to obtain a mixture;

[0040] (3) The mixed liquid and the mixed material are kneaded into a columnar shape (with a diameter of ), to obtain a strip catalyst carrier precursor, drying it in an oven at 80°C for 12 hours, and calcining it in a muffle furnace at 700°C for 5 hours to obtain a catalyst carrier;

[0041] (4) 9.8 g of ammonium molybdate, 5.7 g of metatitanic acid, 4.28 g of potassium nitrate, and 14.0 g of zirconium nitrate were dissolved in deionized water, and an equal volume of the solution was impregnated into the catalyst carrier, dried in an oven at 80°C for 12 h, and calcined in a muffle furnace at 500°C for 3 h to obtain the desired catalyst.

[0042] Example 2

[0043] The method for preparing the sulfur-resistant shift catalyst described in this embodiment comprises the following steps:

[0044] (1) Pour 44.0 g of aluminum nitrate, 16.0 g of cobalt nitrate and 32.8 g of citric acid into a beaker, add an ethanol aqueous solution to completely dissolve them, and obtain a mixed solution, which is stirred and evaporated in an aqueous solution at 80° C. to a certain volume;

[0045] (2) 62.9 g of pseudo-boehmite and 20.0 g of magnesium oxide were mixed uniformly to obtain a mixture;

[0046] (3) kneading the mixed liquid and the mixed material into a columnar shape (with a diameter of ), to obtain a strip catalyst carrier precursor, drying it in an oven at 80°C for 12 hours, and calcining it in a muffle furnace at 700°C for 5 hours to obtain a catalyst carrier;

[0047] (4) 14.6 g of ammonium molybdate and 11.4 g of titanic acid were dissolved in deionized water, and an equal volume of the solution was impregnated into the catalyst support, dried in an oven at 80° C. for 12 h, and calcined in a muffle furnace at 500° C. for 3 h to obtain the desired catalyst.

[0048] Example 3

[0049] The method for preparing the sulfur-resistant shift catalyst described in this embodiment comprises the following steps:

[0050] (1) 36.7 g of aluminum nitrate, 14 g of cobalt nitrate and 27.8 g of citric acid were poured into a beaker, and an aqueous solution of ethanol was added to completely dissolve the mixture, and the mixture was stirred and evaporated in an aqueous solution at 80° C. to a certain volume;

[0051] (2) 78.6 g of pseudo-boehmite and 15 g of magnesium oxide were mixed uniformly to obtain a mixture;

[0052] (3) kneading the mixed liquid and the mixed material into a columnar shape (with a diameter of ), to obtain a strip catalyst carrier precursor, drying it in an oven at 80°C for 12 hours, and calcining it in a muffle furnace at 700°C for 5 hours to obtain a catalyst carrier;

[0053] (4) 10.4 g of ammonium molybdate, 5.7 g of metatitanic acid, and 14.0 g of zirconium nitrate were dissolved in deionized water, and an equal volume of the solution was impregnated into the catalyst support, dried in an oven at 80° C. for 12 h, and calcined in a muffle furnace at 500° C. for 3 h to obtain the desired catalyst.

[0054] Example 4

[0055] The method for preparing the sulfur-resistant shift catalyst described in this embodiment comprises the following steps:

[0056] (1) Pour 25.7 g of aluminum nitrate, 12 g of cobalt nitrate and 20.8 g of citric acid into a beaker, add an ethanol aqueous solution to completely dissolve them, and stir the mixture in an aqueous solution at 80° C. to evaporate to a certain volume;

[0057] (2) Take 84.3 g of pseudo-boehmite and 15 g of magnesium oxide and mix them evenly;

[0058] (3) kneading the mixed liquid and the mixed material into a columnar shape (with a diameter of ), to obtain a strip catalyst carrier precursor, drying it in an oven at 80°C for 12 hours, and calcining it in a muffle furnace at 700°C for 5 hours to obtain a catalyst carrier;

[0059] (4) 9.8 g of ammonium molybdate, 5.7 g of metatitanic acid, and 4.28 g of potassium nitrate were dissolved in deionized water, and an equal volume of the solution was impregnated into a catalyst carrier, dried in an oven at 80° C. for 12 h, and calcined in a muffle furnace at 500° C. for 3 h to obtain a catalyst.

[0060] Example 5

[0061] The method for preparing the sulfur-resistant shift catalyst described in this embodiment comprises the following steps:

[0062] (1) Pour 25.6 g of aluminum nitrate, 12 g of cobalt nitrate and 20.8 g of citric acid into a beaker, add an ethanol aqueous solution to completely dissolve them, and stir the mixture in an aqueous solution at 80° C. to evaporate to a certain volume;

[0063] (2) Take 77.1 g of pseudo-boehmite and 20 g of magnesium oxide and mix them evenly;

[0064] (3) kneading the mixed liquid and the mixed material into a columnar shape (with a diameter of ), to obtain a strip catalyst carrier precursor, drying it in an oven at 80°C for 12 hours, and calcining it in a muffle furnace at 700°C for 5 hours to obtain a catalyst carrier;

[0065] (4) 9.8 g of ammonium molybdate and 11.4 g of metatitanic acid were dissolved in deionized water, and an equal volume of the solution was impregnated into a catalyst carrier, dried in an oven at 80° C. for 12 h, and calcined in a muffle furnace at 500° C. for 3 h to obtain a catalyst.

[0066] Example 6

[0067] The method for preparing the sulfur-resistant shift catalyst described in this embodiment comprises the following steps:

[0068] (1) Pour 44 g of aluminum nitrate, 16 g of cobalt nitrate and 32.8 g of citric acid into a beaker, add an ethanol aqueous solution to completely dissolve them, and stir the mixture in an aqueous solution at 80° C. to evaporate to a certain volume;

[0069] (2) Take 61.4 g of pseudo-boehmite and 25 g of magnesium oxide and mix them evenly;

[0070] (3) kneading the mixed liquid and the mixed material into a columnar shape (with a diameter of ), to obtain a strip catalyst carrier precursor, drying it in an oven at 80°C for 12 hours, and calcining it in a muffle furnace at 700°C for 5 hours to obtain a catalyst carrier;

[0071] (4) 9.8 g of ammonium molybdate and 11.4 g of metatitanic acid were dissolved in deionized water, and an equal volume of the solution was impregnated into a catalyst support, dried in an oven at 80° C. for 12 h, and calcined in a muffle furnace at 500° C. for 3 h to obtain a catalyst.

[0072] Comparative Example 1

[0073] The preparation method of the catalyst described in this comparative example comprises the following steps:

[0074] (1) 87.1 g of pseudo-boehmite, 20 g of magnesium oxide, and 11.42 g of metatitanic acid were mixed evenly, kneaded and molded into a strip catalyst carrier precursor, dried in an oven at 80° C. for 12 h, and calcined in a muffle furnace at 700° C. for 5 h to obtain a catalyst carrier;

[0075] (2) 9.8 g of ammonium molybdate and 12 g of cobalt nitrate were dissolved in deionized water respectively, and an equal volume of the solutions was impregnated into a catalyst support, dried in an oven at 80° C. for 12 h, and calcined in a muffle furnace at 500° C. for 3 h to obtain a catalyst.

[0076] Comparative Example 2

[0077] The preparation method of the catalyst described in this comparative example comprises the following steps:

[0078] (1) 91.4 g of pseudo-boehmite and 25 g of magnesium oxide were mixed evenly, kneaded and shaped to obtain a strip catalyst carrier precursor, which was dried in an oven at 80° C. for 12 h, and calcined in a muffle furnace at 700° C. for 5 h to obtain a catalyst carrier;

[0079] (2) 9.8 g of ammonium molybdate and 12 g of cobalt nitrate were dissolved in deionized water respectively, and an equal volume of the solutions was impregnated into a catalyst support, dried in an oven at 80° C. for 12 h, and calcined in a muffle furnace at 500° C. for 3 h to obtain a catalyst.

[0080] Experimental example

[0081] 1. Catalyst active ingredients

[0082] In the above-mentioned Examples 1-6 and Comparative Examples 1-2 of the present invention, the active component ratios of the catalysts prepared are shown in Table 1 below.

[0083] Table 1 Catalyst formulations for Examples 1-6 and Comparative Examples 1-2

[0084]

[0085] 2. Catalyst activity

[0086] In this experimental example, the catalyst was loaded into the reactor, the raw gas was introduced, the temperature was raised to the test conditions and the conditions were maintained stable for 30 minutes. The chromatogram was started to inject samples, the sample analysis time was 30 minutes, and the injection was repeated 3 times, and the average value of the 3 data was taken.

[0087] Test conditions: catalyst loading 5 mL, reactor inlet temperature: 300 °C, pressure: 4.0 MPa, volume space velocity 2000 h -1 , H2:CO volume ratio = 3:7.

[0088] CO conversion rate = (CO volume content before reaction - CO volume content after reaction) / (CO volume content before reaction * (1 + CO volume content after reaction / 100)) × 100%.

[0089] This experimental example uses an evaluation device with a pressure of 4.0 MPa, a water-gas ratio of 0.3, and a gas-air velocity of 2000 h -1The catalysts prepared in the above embodiments and comparative examples were tested under the conditions of 300°C inlet temperature of the control device, and the test results are shown in Table 2 below. Figure 1 shown.

[0090] Table 2 Catalytic activity evaluation results of the finished catalysts of Examples 1-4 and Comparative Examples 1-2

[0091] catalyst CO conversion rate, % <![CDATA[CH4 content in the tail gas, %]]> Example 1 50.7% 0.38% Example 2 49.2% 0.37% Example 3 48.9% 0.41% Example 4 49.8% 0.40% Example 5 50.3% 0.42% Example 6 48.4% 0.44% Comparative Example 1 45.1% 1.58% Comparative Example 2 44.8% 1.75%

[0092] It can be seen that the cobalt-molybdenum sulfur-resistant shift catalyst of the present invention has the advantages of high shift reaction activity and low methanation reaction activity, and can effectively solve the adverse effects of reduced shift reaction activity, increased methanation reaction activity, and "overheating" of bed temperature caused by methanation side reactions occurring at high catalyst bed temperatures under process conditions of high CO content and low water-gas ratio, and has good application value.

[0093] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A sulfur-tolerant shift catalyst, characterized in that: The catalyst has a support structure as shown in Al2O3-MgAl2O4-CoAl2O4; The sulfur-resistant shift catalyst comprises, based on the total amount, 6-12 wt% of MoO3, 3-4 wt% of CoO, 10-25 wt% of MgO, 57-80 wt% of Al2O3, and 2-10 wt% of metal additive oxide.

2. The sulfur-resistant shift catalyst according to claim 1, characterized in that ,, the metal additive oxide includes at least one of K2O, Zr2O or Ti2O.

3. A method for preparing a sulfur-resistant shift catalyst as claimed in claim 1 or 2, characterized in that: The steps include: (1) mixing aluminum salt, cobalt salt and acid solution, and adding alcohol solution to dissolve them to obtain a mixed solution for standby use; (2) Mixing pseudo-boehmite and magnesium oxide to obtain a mixture for later use; (3) kneading the mixed liquid and the mixed material to obtain a carrier precursor, and performing a first drying and a first calcination treatment to obtain a catalyst carrier; (4) The catalyst carrier is immersed in an active solution containing a molybdenum salt and a metal promoter precursor, and subjected to a second drying and a second calcination treatment to obtain the desired catalyst.

4. The method for preparing the sulfur-resistant shift catalyst according to claim 3, characterized in that: In the step (1): The cobalt salt (in the form of Co 2+ ) and the aluminum salt (in terms of Al 3+ The molar ratio of 1:2-3 is 1:2-3; and / or, The acid solution and the cobalt salt (in the form of Co 2+ The aluminum salt (in terms of Al 3+ The molar ratio of the total amount of the above-mentioned components is 1:0.5-1.5, preferably 1:

1.

5. The method for preparing the sulfur-resistant shift catalyst according to claim 3 or 4, characterized in that: The step (1) further comprises the step of evaporating and concentrating the mixed solution; Preferably, the acid comprises citric acid; Preferably, the alcohol solution comprises an ethanol aqueous solution.

6. The method for preparing the sulfur-resistant shift catalyst according to any one of claims 3 to 5, characterized in that: In the step (2), the magnesium oxide (Mg 2+ ) and the pseudo-boehmite (in terms of Al 3+ The molar ratio of 1:2-3.

7. The method for preparing the sulfur-resistant shift catalyst according to any one of claims 3 to 6, characterized in that: In the step (3), the temperature of the first calcination step is 600-800° C., and the calcination time is 4-6 hours; Preferably, the first drying temperature is 60-100° C., and the drying time is 10-15 hours.

8. The method for preparing the sulfur-resistant shift catalyst according to any one of claims 3 to 7, characterized in that: In the step (4), the molybdenum salt (Mo 3+ ) and the cobalt salt (in Co 2+ The molar ratio of 2-3:1; Preferably, the molybdenum salt comprises ammonium molybdate; Preferably, the metal additive precursor comprises a nitrate of the metal additive, more preferably one of potassium nitrate, zirconium nitrate or metatitanic acid.

9. The method for preparing the sulfur-resistant shift catalyst according to any one of claims 3 to 8, characterized in that: In the step (4), the temperature of the second calcination step is 400-600° C., and the calcination time is 2-4 hours; Preferably, the second drying temperature is 60-100° C., and the drying time is 10-15 hours.

10. Use of the sulfur-tolerant shift catalyst according to claim 1 or 2 or the sulfur-tolerant shift catalyst prepared by the method according to any one of claims 3 to 8 in a carbon monoxide shift process.

Citation Information

Patent Citations

  • Method for preparing wide-temperature sulfur-tolerant shift catalyst by taking heteropolyacids as precursors

    CN103949285A

  • Cobalt- and molybdenum-containing mixed oxide catalyst, and production and use thereof as water gas shift catalyst

    US20140138586A1

  • Process to conduct a reverse water-gas shift reaction in an electrified fluidized bed reactor

    WO2023148000A1